Co-production of biohydrogen and biomethane utilizing halophytic biomass Atriplexcrassifolia by two-stage anaerobic fermentation process - Nawaz, Ali; Aamir, Farheen; Huang, Rong; Haq, Ikram ul; Wu, Fangyu; Munir, Marium; Chaudhary, Rida; Rafique, Ayesha; Jiang, Kankan (Frontiers in Chemistry, 2023)
The excessive use of fossil has resulted in the drastic exhaustion of natural energy sources, leading to environmental challenges and energy crises. Owing to rising energy demand there is a dire need to shift towards renewable energies from lignocellulosic biomass. The present study assessed the co-production of biohydrogen (H2) and biomethane (CH4) by utilizing a less explored halophyte Atriplexcrassifolia. Various reaction parameters were evaluated for their effect on biohydrogen and biomethane production in batch experiments. One parameter at a time experimental strategy was chosen for production optimization. Hydrogen and methane yields along with their production rates were assessed at different incubation times, temperatures, pH, substrate concentrations, and inoculum sizes in acidogenesis and methanogenesis stages, respectively. In the first stage, maximum cumulative hydrogen production of 66 ± 0.02 mL, with hydrogen yield of 13.2 ± 0.03 mL/g, and hydrogen production rate (HPR) of 1.37 ± 0.05 mL/h was attained when the reaction mixture (5 g Atriplexcrassifolia and 10 mL pretreated sewage sludge) was processed at 37°C and pH 5.5 after 48 h of incubation. While in the second stage, maximum cumulative methane production, i.e., 343 ± 0.12 mL, methane yield (MY) of 8.5 ± 0.07 mL/mL, and methane production rate (MPR) of 0.8 ± 0.05 mL/h was achieved after 18 days of incubation of reaction mixture (40 mL of hydrogenic slurry with 80 mL inoculum) at 45°C and pH 8. Furthermore, a 51% and 24% rise in biohydrogen and biomethane production respectively were recorded when the gases were produced at these optimized reaction conditions. The results ensure halophyte Atriplexcrassifolia as an imperative renewable energy resource and proposed that effective optimization of the process further increased the coproduction of biohydrogen and biomethane.